Productivity of hired and family labour and determinants of technical inefficiency in Ghana's fish farms - Edward E. Onumah; Gabriele Hoerstgen-Schwark; Bernhard Brümmer (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2009)
This paper examines the productivity of hired and family labour and determinants of technical inefficiency of fish farms in Ghana. A modified Cobb-Douglas stochastic frontier production function which accounts for zero usage of family and hired labour is employed on cross-sectional data of 150 farmers collected in 2007. The results reveal that family labour, hired labour, feed, seed, land, other cost and extension visit have reasserting influence on fish farm production. Findings also show that family and hired labour used for fish farming production in Ghana may be equally productive. The combined effects of operational and farm specific factors (age, experience, land, gender, pond type and education) influence technical inefficiency although individual effects of some variables may not be significant. Mean technical efficiency is estimated to be 79 percent. Given the present state of technology and input level, the possibility of enhancing production can be achieved by reducing technical inefficiency by 21 percent through adoption of practices of the best fish farm.
Keywords: 330; Ghana; fish farms; technical inefficiency; hired and family labour; stochastic frontier.